2006
DOI: 10.1096/fj.06-6910com
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of diabetes by imatinib mesylate (Gleevec®): role of ‐cell NF‐KB activation and anti‐apoptotic preconditioning

Abstract: It was recently reported that tyrosine kinase inhibitor imatinib mesylate (Gleevec) improves Type 2 diabetes, possibly by decreasing insulin resistance. However, as both Type 2 and Type 1 diabetes are characterized by beta-cell dysfunction and death, we investigated whether imatinib counteracts diabetes by maintaining beta-cell function. We observed that imatinib counteracted diabetes in two animal models, the streptozotocin-injected mouse and the nonobese diabetes mouse, and that this was paralleled by a part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
102
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(107 citation statements)
references
References 36 publications
4
102
0
1
Order By: Relevance
“…In this regard, we note that Hagerkvist et al recently showed that imatinib ameliorates type 2 diabetes in rats by lowering insulin resistance (45). However, in a related study (22), the authors concluded that imatinib treatment preserved ␤ cell viability through an Abl-dependent inhibition of NFB. Our studies suggest that an Abl-independent mechanism of action is a key to the affects of imatinib in the T1D setting.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In this regard, we note that Hagerkvist et al recently showed that imatinib ameliorates type 2 diabetes in rats by lowering insulin resistance (45). However, in a related study (22), the authors concluded that imatinib treatment preserved ␤ cell viability through an Abl-dependent inhibition of NFB. Our studies suggest that an Abl-independent mechanism of action is a key to the affects of imatinib in the T1D setting.…”
Section: Discussionmentioning
confidence: 72%
“…Furthermore, imatinib can be administered for as short as 10 weeks with long-lasting effects working through the inhibition of PDGFR. These results, coupled with recent studies demonstrating a direct protective effect of imatinib on type 2 diabetes in rodents (22) suggests that this molecule and other kinase inhibitors such as sunitinib have potential as a therapeutic to treat patients with this disease.…”
mentioning
confidence: 68%
“…Although a decrease was observed at week 4, this was not significant (data not shown, P ¼ 0.06). Third, amelioration of diabetes by imatinib (Gleevec s ) has been reported in animal models (Hagerkvist et al, 2007) and in human (Veneri et al, 2005). This unexpected effect was related to the protective effect of imatinib on b cells by an antiapoptotic action through NF-kB activation.…”
Section: Discussionmentioning
confidence: 95%
“…In support of this, improved glycaemic control has also been observed following imatinib treatment in animal models of diabetes. In streptozotocin-induced and spontaneous (non-obese diabetic and db/db) mouse models of diabetes, imatinib has been shown to preserve islet b-cell function, in part through the suppression of c-abl-mediated islet cell apoptosis (Hagerkvist et al 2007, Han et al 2009). Imatinib and other inhibitors of PDGFR have also been shown to prevent and even reverse diabetes in nonobese diabetic mice through a mechanism that may involve suppression of a PDGF-induced inflammatory response (Louvet et al 2008).…”
Section: Introductionmentioning
confidence: 99%